Awareness of COVID-19 Infection and its Safety Protocols among Health Care Workers in Pakistan: A Cross Sectional Study on Knowledge, Attitude and Practice (KAP) - Mahwish Akhtar Qureshi, Maliha Akhtar Qureshi, Qurat-Ul-Ain, Asem Hameed, Najeeb Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To draw a comparative analysis of the levels of awareness of COVID-19 pandemic and its protective measures amongst health care workers (HCWs). Materials and Methods: This cross sectional study on Knowledge, Attitude and Practice (KAP) was conducted at PIMS Hospital, Islamabad from 1st August 2020 to 30th September 2020. 156 professionals in the hospital including doctors and paramedics, who directly or indirectly came in contact with or managed COVID-19 patients, were included in the study with their consent and were provided with a questionnaire of 22 questions which comprised of answers of ‘yes’, ‘no’ or ‘I don’t know’. All participants were divided into two groups; the doctors were assigned Group 1 while the paramedics Group 2. Their answers were studied and overall KAP and comparison was analyzed using SPSS, v 22; IBM Corporation, Armonk, NY. The correct responses were considered ‘Poor’ (<70%), ‘Good’ (70-90%) and ‘Very Good” (>90%). Results: The difference in gender population between two groups was not significant. The difference in correct knowledge, attitude and practice between two groups was statistically significant. Conclusion: The attitude and practice about COVID-19 and its preventive measures was good in all professionals, though the doctors had very good (>90%) attitude. The knowledge was poor (<70%) in paramedics. The awareness programs are still required to continue better understanding and practice of COViD-19 especially in paramedics. Keywords: COVID-19, Corona, Knowledge, Attitude, Practice, Healthcare workers.